Global Impact of Top Management on Branding and Performance: Dampak Global dari Manajemen Puncak terhadap Pencitraan Merek dan Kinerja - Rochman, Saiful; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how top management commitment to ISO 9001:2015 quality management system influences company branding and employee performance, with employee commitment moderating this relationship. Conducted in a cardboard packaging industry in Sidoarjo, East Java, Indonesia, the research involved 105 employees selected through purposive sampling. Data was collected via personal questionnaire surveys and analyzed using Structural Equation Modeling Partial Least Square (SEMPLS). Results show that top management commitment significantly impacts company branding and employee performance. However, employee commitment's moderating effect on the relationship between top management commitment and company branding was found insignificant due to incomplete socialization of the quality management system among employees, while it significantly moderated the relationship between top management commitment and employee performance. This study underlines the importance of top management commitment in ISO 9001:2015 implementation for improving company branding and employee performance and suggests the need for comprehensive socialization of quality management systems. Hightligh: Top management drives branding and performance. Employee commitment moderates top management's influence. Incomplete socialization affects employee commitment's moderating effect. Keywords: ISO 9001:2015, Top management commitment, Company branding, Employee performance, Moderation.